The Hierarchical Planning of Production in Agro Alimentary Environment: Case of Interdependent Products - Erromdhani, Ridha; Mabrouk, Najeh Ben; Rebai, Abdelwaheb (Journal of Informatics and Mathematical Sciences, 2010)
In this paper, we are interested to the problem of planning inside the agro-alimentary industry. In this context, we have take into account many specific constraints such us products interdependence and the existence of many changeable production procedures. We propose a hierarchical model that respects the real capacities of the workshop and the product interdependence. Indeed, we have established a mathematical model according to different production levels. While taking into account real capacities of the shop and the interdependencies between the products, the results of our formulation are satisfactory in terms of quality of solution and time requirements. It's shown that our model is able to reach all optimal solutions for all treated models and for all system levels.